The NET, the trap and the pathogen: neutrophil extracellular traps in cutaneous immunity. Issue 3 (March 2015) - Stephan, Alexander; Fabri, Mario
Abstract Neutrophil extracellular traps (NETs), large chromatin structures casted with various proteins, are externalized by neutrophils upon induction by both self‐ and non‐self‐stimuli. It has become clear that NETs are potent triggers of inflammation in autoimmune skin diseases. Moreover, the ability of NETs to trap pathogens suggests a crucial role in innate host defense. However, the outcome of the encounter between pathogens and NETs remains highly controversial. Here, we discuss recent insights into the morphology and formation of NETs, their role in skin inflammation and how NETs might contribute to host protection in skin infection.